Diversity in Entrepreneurship: Ethnic and Female Roles in Urban Economic Life - Tuzin Baycan Levent; Enno Masurel; Peter Nijkamp (Fondazione Eni Enrico Mattei (FEEM), 2003)
The aim of this paper is to investigate the phenomenon of ethnic female entrepreneurship in urban economic life. The focus of the research is on the attitude and behaviour of Turkish female entrepreneurs in Amsterdam. The main fascinating question is: Are ethnic female entrepreneurs special ethnic entrepreneurs or special female entrepreneurs? This paper provides an answer to this question on the basis of field surveys. The results of the case study research on Turkish female entrepreneurs in Amsterdam show that the ethnic female profile is a special female profile and that Turkish female entrepreneurs are special female entrepreneurs, particularly in terms of personal and business characteristics, driving forces and motivations. They appear to combine their ethnic opportunities with their personal characteristics (and other opportunities) in the urban market, and to have a successful performance. This is also caused by the fact that they have become service providers not only for their own ethnic groups, but also for other groups in the city.Keywords: Ethnic female entrepreneurship, diversity in entrepreneurship, ethnic female profile, Turkish female entrepreneurs
Keywords: M13; 330; Entrepreneurship-Ansatz; Frauen; Türken; Amsterdam